Analysis Of Patient Perceptions, Awareness, Experience And Expectations Of The Role Of Pharmacist In Counseling Service At Pharmacies - Dyah Ayu Kusumaratni; Eko Yudha Prasetyo; Indah Srihartini; Shofiatul Fajriyah; Widhi Astutik; Aprillia Putri G.R (Sean Institute, 2024)
Counseling services are a form of communication between pharmacists and patients in pharmaceutical services with the aim of increasing patient understanding of drug use and preventing medication errors. The presence of pharmacists is very necessary to be able to meet the diverse demands of society to be able to provide information regarding the correct use of medicines so that they can increase public knowledge. The interactions that occur between pharmacists and patients in counseling services will have an influence on public assessment. This research was conducted with the aim of knowing patients' perceptions, awareness, experiences and expectations of the role of pharmacists in counseling services in pharmacies. Method: The research is descriptive with a cross sectional design with a purposive sampling technique, the number of subjects involved was 143 respondents. Descriptive data analysis and normality test. Results: showed that 67.13% of patients had good awareness. As many as 53.14% of patients had a good perception. Then as many as 100% of patients had good hopes, and as many as 72.02% of patients had good experiences. Conclusion: the overall category shows the percentage of patients who have good perceptions, awareness, expectations and experiences regarding the role of pharmacists in counseling services in pharmacies.